PASSION CONFLICT IN A JURIDICAL DISCOURSE - Pistori, Maria Helena Cruz (Laboratório Editorial FCL-UNESP, 2010)
This paper is concerned with the use of the passions as persuasive argument, as advocated by Aristotelian Rhetoric. The progress of studies in contemporary discourse enables us to analyze the configurations of passion occurring in the juridical process chosen, primarily outrage and compassion. The theoretical foundation of the study is the semiotics of the School of Paris, especially the tensive semiotics. We seek to observe the construction of the pathemic roles of enunciators iteratively throughout the process, for this allows a potential predictability of their actions. We add, in concluding remarks, some reflections on the ethical standards of the passions in our society.